Global and local parameters for characterizing and modeling external corrosion in underground coated steel pipelines: A review of critical factors - Kim, Changkyu; Chen, Lin; Wang, Hui; Castaneda, Homero (Journal of Pipeline Science and Engineering, 2021)
External corrosion assessments of pipeline systems encompass two critical factors: time and space (location). Field measurement databases, laboratory testing, and theoretical prediction studies have been reported, based on continuous monitoring, survey and on-site characterization techniques, and controlled and simulated laboratory-scale environment studies. Theoretical models have identified several critical factors in assessing external corrosion for buried structures at different scales. This work presents a review of critical parameters for characterizing, modeling, and assessing the corrosion process in buried pipelines. A multiscale approach is used to integrate factors identified from field measurements, laboratory testing, and data-driven and computer-based models. Furthermore, we elucidate the importance of macro parameters and the influence of their spatial distribution on the initiation and propagation of local corrosion mechanisms with their corresponding local (micro scale) conditions. This work also reviews the critical parameters and approaches used for deterministic, semi-empirical, probabilistic, and data-driven modeling, defining the scope of global versus local factors for external corrosion at the soil/steel pipeline interface.